AN INTEGRATED MODEL FOR APPLYING AGILE SIX SIGMA TO CONTROL PRODUCT QUALITY - Jasim Hussein Znad (Scholar Express Journals, 2022)
One of the modern approaches followed to reach a high degree of quality and excellence in products is the six sigma approach. For the purpose of applying this approach, organizations must develop an integrated plan to control product quality that includes setting standard specifications starting with the materials used and passing through the production processes and ending with the specifications of the final products, as well as Determine the methods of examination, testing, methods of sampling, determine what is acceptable and conform to the specifications, and take the necessary measures to reduce deviations from the established specifications in a way that contributes to raising the efficiency of the production system
Keywords: six sigma; single sampling plan; quality control panels; operation curve